An updated meta-analysis of partial splenic embolization versus splenectomy in the treatment of hypersplenism due to cirrhosis. Issue 5 (1st June 2022) - Huang, Yiyang; Ren, Dongqing; Gao, Feng; Ding, Yiwen; Cheng, Hong; Huang, Xiangzhong; Xu, Xinjian
Abstract: Objective: To evaluate the efficacy and safety of partial splenic embolization (PSE) versus splenectomy (SP) for hypersplenism. Material and methods: Pubmed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, and Chinese Science and Technology Periodical Database (VIP) databases were systematically searched to identify all relevant studies. Stratified meta-analysis was also conducted to control the influence of confounding factors on the research results Results: Twenty-three studies comparing PSE with SP involving a total of 1849 hypersplenism patients were selected. Postoperative increased level of platelet (PLT) [mean difference (MD) = −65.51; 95% confidence interval (CI), −81.33 to −41.69 ; p < .00001] were better in SP than in PSE; however, PSE was associated with less operation time (MD = −53.47; 95% CI, −65.01 to −41.94; p < .00001), less intraoperative blood loss (MD = −61.58; 95% CI, −80.35 to −42.82; p < .00001), shorter hospital stay (MD = −2.98;95% CI, −4.07 to −1.88; p < .00001) and lower complication rate [odds ratio (OR) = 0.53; 95% CI, 0.32 to 0.90; p = .02] compared with the SP. Meanwhile, there was no significant difference in postoperative increased level of white blood cells (WBC) (MD = −1.02; 95% CI, −2.16 to 0.11; p = .08) and postoperative increased level of hemoglobin (HB) (MD = −4.09; 95% CI, −14.06 to 5.88; p = .42) between PSE and SP group. Conclusion: PSE had similar efficacy with SP in improving postoperative PLT, WBC, and HB levels. Moreover, PSE had the advantages of less trauma and fewer complications as well as faster recovery when compared with SP. Therefore, we tended to be cautious about SP and considered that patients with hypersplenism might benefit more from PSE.